The Impact of Three Genospecies of Borrelia on Expression of Genes Associated with Chemokines and Their Receptors in Normal Human Dermal Fibroblasts in Vitro. (May 2014) - Gola, J.; Dudek, S.; Jasik, K.; Solarz, K.; Muc-Wierzgoń, M.; Kokot, T.; Nowakowska-Zajdel, E.; Ziółko, E.; Fatyga, E.; Mazurek, U.
An important role in pathomechanism of Lyme disease is played by the ability of spirochetes to spread within tissues, and to adhere (to platelets, erythrocytes and vascular epithelium). The principal factors regulating that process are chemokines, cytokines and adhesion particles. The aim of this study was to select genes related to the chemokines and their receptors, differentiating the type of infection in the system model, i.e. a culture of normal human diploid fibroblasts infected with three different spirochete genospecies: B. afzelii, B. garinii and B. burgdorferii sensu stricto, by comparing the infected fibroblast culture with that of the control fibroblast. The differences in the expression of genes selected on the basis of a scientific database Affymetrix were analysed by comparing transcriptomes from the four cultures of fibroblasts, using the oligonucleotide microarrays HG_U133A. In the result of infection of fibroblast cultivation with a specific Borrelia genospecies, a variable expression of the chemokines and their receptors, specific for one genospecies was observed. The fibroblast infected with B. afzelii expressed CCL4, CCL1, CCL2 and CCR10; with B. garinii - CXCL12, IL6, CCR3 and CXCR5; and with B. burgorferii sensu stricto - CCL5, CCR1, CCL3, CCL16, CXCR6, IL8, CXCR7 and CXCR3.